WEB-BASED LEARNING MATERIAL FOR RAISING STUDENTS’ LEVELS OF AWARENESS AND USE OF READING STRATEGIES - Dirgantari, Alfi Suci; Susantiningdyah, Healty (PUPIL: International Journal of Teaching, Education and Learning, 2021)
Being active readers is beneficial to students’ academic success. To reach that, students need to understand what the reading strategies are, and how, when, and where to use them. Unfortunately, most of the students in ITK are not using the strategies effectively, which then hinders their comprehension of English texts. To help improve students’ reading ability through the usage of reading strategies, this research proposed to develop a web-based learning material containing materials and exercises in using reading strategies in an academic reading activity. The development model of the e-learning material is following the 4-D model: define, design, develop, and dissemination. The data collected were in the form of feedbacks from peer-review (qualitative) and developmental testing (quantitative). The feedback from peer-review contained suggestions for the improvement of the website; the testing resulted in the score for the web. With the average score of 3.63 on the Likert scale, most students believed that this website would be able to help them become more familiar with the use of reading strategies in academic reading.